Estimating the global burden of scabies: what else do we need?. (9th July 2020) - Cox, V.; Fuller, L.C.; Engelman, D.; Steer, A.; Hay, R.J.
Summary: Scabies is one of the most common disorders identified in any estimate of global skin disease prevalence. Furthermore, quantifying its impact on individuals and societies has been problematic. There has been a lack of clear case definitions and laboratory tests. There have been few epidemiological studies, particularly those focusing on low‐income countries, variation in prevalence within high‐income countries, or estimates of the effect of scabies on health beyond the skin, such as renal disease or mental wellbeing. Economic studies are also lacking. However, the new strategy of integrating surveillance for skin Neglected Tropical Diseases may well produce advancements on these issues, in addition to providing an overarching structure for health improvement and disease control. Abstract : What is already known about this topic? There is a dearth of information on the global impact of scabies. This review article reviews the current literature and details missing data. The designation of scabies as a Neglected Tropical Disease has added urgency to the need to carry out further research on the epidemiology and impact of this infection. What does this study add? This study provides an up‐to-date critique of the current state of our understanding of the global impact of scabies and addresses how to fill the gaps in our knowledge. Plain language summary available online